SUBSTANTIATION OF SYSTEM COMPONENTS MORAL EDUCATION OF THE FUTURE BORDER OFFICERS (Pedagogy of Higher and Secondary Education, 2004)
In the article, the author discredits the purposes, components, objects, content of moral bringing up of future officers.